2017
DOI: 10.1111/issr.12129
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of pension reform in Georgia: Non‐contributory pensions and elderly poverty

Abstract: Georgia's national social security system offers almost universal non‐contributory basic pension coverage. The basic pension has, to date, proved effective in dealing with old‐age poverty. But Georgia's fiscal constraints and ageing population also highlight the importance of improving the pension system, in order to ensure its sustainability. This article presents policy reform choices, which suggest that, in Georgia, pension reform might include increasing the statutory retirement ages and reducing the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Namibia’s universal non‐contributory social pension has contributed to a 22 per cent decrease in severe poverty (Levine, van der Berg and Yu, 2011). In Georgia, poverty among older adults decreased from 22 per cent in 2006 to 15 per cent in 2013, largely because of its non‐contributory social pension (Nutsubidze and Nutsubidze, 2015). Poverty and hunger among recipients of Uganda’s non‐contributory social pension dropped by 16 per cent and 23 per cent, respectively, in the two years following initial receipt of this benefit (Kidd, 2016).…”
Section: Evidence From Other Developing Countriesmentioning
confidence: 99%
“…Namibia’s universal non‐contributory social pension has contributed to a 22 per cent decrease in severe poverty (Levine, van der Berg and Yu, 2011). In Georgia, poverty among older adults decreased from 22 per cent in 2006 to 15 per cent in 2013, largely because of its non‐contributory social pension (Nutsubidze and Nutsubidze, 2015). Poverty and hunger among recipients of Uganda’s non‐contributory social pension dropped by 16 per cent and 23 per cent, respectively, in the two years following initial receipt of this benefit (Kidd, 2016).…”
Section: Evidence From Other Developing Countriesmentioning
confidence: 99%
“…See, for instance,Nutsubidze and Nutsubidze (2015). 14 All social assistance data in this subsection come from the Social Service Agency of the Ministry of Labor, Health, and Social Affairs of Georgia, http://ssa.gov.ge/index.php?sec_id=610&lang_id=ENG.…”
mentioning
confidence: 99%
“…Therefore, discontinuing the programme at the expiration of the government revealed that it was not a policy rather a political tool. Old age cash support has proved positive in dealing with old age issues, promoting longevity and fighting poverty (Edebalk & Olsson, 2010;Sanyal & Singh, 2013;Kuss & Llewellin, 2016;Nutsubidze & Nutsubidze, 2017). Establishing a successful social security program that will provide cash support for the senior citizens will be a step in the right direction toward ensuring the welfare of senior citizens in Nigeria.…”
Section: Discussion Of Findingsmentioning
confidence: 99%